Takut Akan Allah Menurut Bapa-Bapa Philokalia Dan Implikasi Bagi Gereja Masa Kini - okto vianus Polulu (Jurnal Teologi Cultivation, 2020)
Philocalia is a collection of texts written in the fourth and fifteenth centuries by the fathers and fathers of the Church in the Orthodox Christian tradition. Fearing God is keeping God's commandments, having God's love and souls purified and united with God in salvation This article is a review, there are 7 main points of discussion. First Repentance is leaving the old man (Eph 4:22, Col 3: 9) . The second is to control oneself is to be “watchful” (1Th 5: 6, 1Th 5:10 Rev. 16:15) so as not to get lost. Third, safeguarding knowledge is to know about God. Four, doing God's commandments is that we give hope to Him with full obedience and hope of being saved by God (Psalm 78: 7, Proverbs 19:16). The five fear with all your heart is a heart that is in Divine light. The six Souls free from sin are those who have run to heavenly calls (Phil. 3:14) to attain a goal or perfection. The goal, to purify the soul is, the soul is already in Divine light.Keywords: The soul is purified; Allah's love; Control;  Keep the commandments of Allah. Philokalia adalah kumpulan teks di tulis pada abad keempat dan abad ke lima belas oleh para rahip dan para Bapa Gereja dalam tradisi Kristen Ortodoks. Takut akan Allah adalah melakukan perintah-perintah Allah, memiliki Kasih Allah dan Jiwa di murnikan serta disatukan dengan Allah dalam keselamatan Artikel ini adalah sebuah ulasan,  ada 7 pokok pembahasan Pertama Pertobatan ialah meninggalkan manusia lama (Ef 4:22, Kol 3:9). Kedua Mengontrol diri ialah “berjaga-jagalah” (1Tes 5:6, 1Tes 5:10 Why 16:15) supaya tidak tersesat. Ketiga, Menjaga Pengetahuan ialah, untuk tahu tentang Allah. Empat, melakukan perintah Allah ialah kita menaru harapan kepada-Nya dengan penuh ketaatan serta harapan akan diselamatkan oleh Allah (Mzm 78:7, Ams 19:16). Kelima takut dengan sepenuh hati ialah hati yang berada dalam cahaya Ilahi. Enam Jiwa terbebas dari dosa ialah, Jiwa yang telah berlari pada pangilan sorgawi (Flp 3:14) untuk mencapai tujuan atau kesempurnaan. Tuju, Memurnikan jiwa ialah, jiwa telah berada dalam cahaya Ilahi.Kata Kunci: Jiwa di murnikan; Kasih Allah; Mengontrol; Melakukan perintah-perintah Allah.